Maria Aragão: a trajetória de uma médica e militante comunista no Brasil do século XX - Pinto, Rosyjane Paula Farias (Universidade do Vale do Rio dos Sinos, 2022)
This thesis aims to analyze the trajectory of the character Maria Aragão, who acted as a doctor and militant of the Communist Party in the state of Maranhão in the 20th century. It proposes to research the history of a woman from a social place inscribed in the trajectory of life marked by the desire for social and cultural transformation. As a woman of poor origin, Maria Aragão, born in the interior of Maranhão, entered the medical course in the 1930s, in the city of Rio de Janeiro, graduating in 1942. In 1945, she joined the in the capital of Brazil, to the Brazilian Communist Party - PCB, returning to Maranhão to direct the party, becoming one of the main leaders of the left. During the civil-military dictatorship, she was persecuted, imprisoned and tortured. Her history was remarkable for the fight for social justice, defense of women's rights and strengthening of democracy. The sources of this thesis are of varied origin: testimonies of Maria Aragão, documentary about her, newspapers from the mid-20th century and documents of repression (DOPS). The research is located in the field of social history and is inspired by some methodological issues of micro-history, having the name “Maria Aragão” as a guideline to achieve a holistic understanding of the different situations that can be perceived from a life. Concepts such as trajectory, in the perspective that it cannot be unique or closed; memory, considering that it can be both individual and collective, as we are showing a character in his social place; as well as feminism, as a cultural change in behavior that is being presented by crooked paths. Maria Aragão fought to break paradigms in a sexist and prejudiced society, needing to create a network of relationships so that she could achieve success in the professional and political field and be inscribed in the history of Maranhão.
Keywords: Maria Aragão; Partido Comunista Brasileiro; Relações sociais; Ditadura Civil-Militar; Feminismo; Brazilian Communist Party; Social relations; Civil-Military Dictatorship; Feminism; ACCNPQ::Ciências Humanas::História